PENGETAHUAN DAN PENERIMAAN TEKNOLOGI GIZI DI FASILITAS PELAYANAN KESEHATAN: SURVEI PADA GENERASI X DAN Y - Ika Mukti Virgiyanti; Ika Mukti Virgiyanti; Tonang Dwi Ardyanto; Nur Hafidha Hikmayani (GIZI INDONESIA, 2022)
The study aims to assess the difference in knowledge and acceptance levels towards nutritional technology between Generation X and Y nutritionists working in healthcare facilities in East Java Province, Indonesia. This study focused on the quantitative method which a cross-sectional survey applied a purposive sampling method to recruit nutritionists. The online questionnaire was prepared to assess knowledge and acceptance of nutritional technology and circulated to WhatsApp and Telegram groups. The researchers recruited 355 participants based on the inclusion criteria and completed the questionnaire. The data were analyzed using Chi-squared Test and Pareto Principle. This study showed that the knowledge levels among Generations X and Y were 76,8 percent and 83,2 percent, respectively, whereas the acceptance levels were both lower at 72,0 percent and 74,9 percent, respectively. Further analyses showed no different in both the knowledge level (????2 = 2.295, p-value = 0.167) and the acceptance level (????2 = 0.386, p-value = 0.617) of nutritional technology between the two generations. In addition, this study concluded that despite having good knowledge of nutritional technology, Generation Y nutritionists' acceptance of the technology was still less than expected. This information can be used as an evaluation material for Persagi to encourage their members to increase their digital literacy related to nutrition technology by the generation characteristics of the nutritional workforce